Systemic Blockade of TNF-α does not Improve Insulin Resistance in Humans - Ferraz-Amaro, I.; Arce-Franco, M.; Muñiz, J.; López-Fernández, J.; Hernández-Hernández, V.; Franco, A.; Quevedo, J.; Martínez-Martín, J.; Díaz-González, F. (Hormone and Metabolic Research, 2011)
The purpose of this study was to determine whether long-term modulation of inflammatory activity by tumor necrosis factor (TNF)-α inhibitors has some influence on insulin resistance (IR). 16 active rheumatoid arthritis (RA) patients without CV risk factors treated with anti-TNF-α agents were included in this study. RA activity by disease activity score 28, IR by HOMA2-IR, body composition by impedance analysis, physical activity by accelerometry, abdominal fat distribution by magnetic resonance imaging, and serum level of key adipokines by ELISA were measured at baseline and during a 1-year follow-up period. Patient body mass index increased significantly (26.94±3.88 vs. 28.06±4.57 kg/m2, p=0.02) after 1 year of treatment. Body composition, in terms of fat and fat-free mass, remained unchanged except for a significant elevation in body cell mass (25.50±4.60 vs. 26.60±3.17 kg, p=0.02). Basal levels of IR in the RA patients included in this study were significantly higher than healthy controls (1.6±0.8 vs. 1.11±0.56, p=0.011) but did not change during the follow-up. Nor did basal concentrations of adiponectin, visfatin, leptin, ghrelin, resistin, and apelin in response to anti-TNF-α treatment; only retinol-binding protein 4, showed a significant increase (51.7±32.7 vs. 64.9±28.4 μg/ml, p=0.03) at the end of the study. IR, adiposity distribution, and serum levels of most adipokines are not significantly affected by long-term inhibition of TNF-α in RA patients. Our data suggest that although systemic blockade of TNF-α exerts an anticachectic effect in RA patients, it does not seem to play a major role in IR.
Keywords: insulin resistance; inflammation; anti-TNF-α compounds; rheumatoid arthritis